STEVENS-JOHNSON SYNDROME SECONDARY TO USE OF AMOXICILLIN - Rezende, Fernanda Coelho (2014)
The Stevens-Johnson Syndrome, responsible for severe mucocutaneous lesions, usually occurs after exposure to certain medications or after infection and may be related to autoimmune events. The authors describe the case of a patient of 47 years who presented the pathology after being subjected to therapy with amoxicillin. After hospitalization and treatment, it showed satisfactory recovery without presenting significant sequelae.